(untitled) (Research, Society and Development, 2022)
Studies involving Engineered Cementitious Composites (ECC) started more than 30 years ago and are still under constant development. ECC has superior mechanical properties when compared to conventional concretes, mainly the characteristics related to tensile behavior. Therefore, the addition of polymeric fibers is essential in the development and response of this composite, so that microcracking occurs and, consequently, resilience and ductility are achieved. The ECC is basically constituted by hydraulic binders, pozzolans, fine aggregates, chemical additives, polymeric fibers in contents close to 2% (by volume) and low water/binder ratio. Thus, the objective of this study is to identify the impact of different pozzolanic materials (fly ash and silica fume), evaluating the rheological and mechanical behavior of the ECC matrix. The mechanical properties evaluated were compressive strength and flexural tensile strength at 7 and 28 days of age. Three cementitious matrices were developed for ECC, with different pozzolans and proportions. It was observed that the matrices containing silica fume obtained better results, both in the fresh state and in the hardened state, mainly due to their granulometry and pozzolanic activity.